Fatwa MUI Terhadap Keharaman Bunga Bank Konvensional Dalam Pandangan Masyarakat Desa Paya Perupuk Kecamatan Tanjung Pura Kabupaten Langkat - Cintana Zulkarnain Putri, Rani Febriyanni, Khairunnisa (Mediation : Journal Of Law, 2022)
Based on the data obtained by the author, it is known that 73% of students still have relatively poor metacognitive abilities. This is caused by several things, including students' lack of interest in learning activities in the field of study of Islamic Religious Education, the learning process still relies on the teacher as the provider of all material information related to the field of study of Islamic Religious Education and students have not been actively involved as learning subjects. According to the teacher in the field of Islamic religious education at Tunas Mandiri Private Middle School, he explained that students' metacognitive abilities in Islamic religious education learning activities were included in the low criteria because students had not been able to fully understand the subject matter given by the teacher in the Islamic religious education study field. The background of this problem makes researchers interested in proposing research using a classroom action research model to find out whether there is an increase in metacognitive abilities through the concept of Spiritual Quotient which can be identified through the application of action interventions for 3 (three) cycles. Based on the results of observations, interviews and test instruments used by researchers, data can be obtained, namely the Spiritual Quotient Concept can improve learning outcomes in the subject of Islamic Religious Education for Class VIII students of Tunas Mandiri Private Middle School with a percentage increase, namely from the pre-cycle the completeness value of students only reaches 29 .8 % students. Then in the first cycle, the percentage of students' completeness score was 45.9, an increase of 16.1 from the pre-cycle. In cycle II, the percentage of mastery learning was achieved by 78.4%, there was an increase in student mastery by 32.5 from cycle I. In Cycle III, learning mastery was achieved by 100, an increase from cycle II. So, there is an increase between cycle II to cycle III, namely 21.6. If taken into account from the pre-cycle to the third cycle there is an increase in the level of 70.2. So it can be concluded that the application of the Spiritual Quotient Concept can improve students' ability to improve metacognitive abilities.